2000
DOI: 10.1007/s007010070038
|View full text |Cite
|
Sign up to set email alerts
|

Tethered Cord Syndrome in Adults

Abstract: The patients presenting with low back pain and sciatica responded to surgery better than those with sphincter problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 21 publications
0
51
0
1
Order By: Relevance
“…18,20 Adults may also present because of retethering from scar tissue formation following an initial operation for spinal dysraphism. 1,6,11 Retethering is considered a relatively common postoperative complication following correction of pediatric spinal dysraphism. 6,9 No studies were found analyzing the pathophysiology of retethering following operative intervention of pediatric TCS and spinal dysraphism.…”
Section: Theorized Pathophysiology Based On Retrospective Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…18,20 Adults may also present because of retethering from scar tissue formation following an initial operation for spinal dysraphism. 1,6,11 Retethering is considered a relatively common postoperative complication following correction of pediatric spinal dysraphism. 6,9 No studies were found analyzing the pathophysiology of retethering following operative intervention of pediatric TCS and spinal dysraphism.…”
Section: Theorized Pathophysiology Based On Retrospective Analysismentioning
confidence: 99%
“…1,6,9,10,15 Unlike children, adult symptomatology is slightly different, with pain being the most common presenting symptom (rare in children 4 ), and this is followed by sensory disturbances, motor dysfunction and weakness, and urinary dysfunction. 1,2,13,15,18,20 Similar to the pediatric population, surgical intervention to release the adult tethered cord has proven to be successful in preventing further deterioration as well as sometimes improving symptoms and deficits. Thus, cord release has increasingly been accepted as a necessary intervention in symptomatic patients.…”
mentioning
confidence: 99%
“…From the original work of Pang and Wilberger 67 onward, many authors have commented on the roles of trauma and vigorous activity in the precipitation of symptoms and signs; 1,20,26 however, this association seems to be less prominent among adults with myelomeningocele and symptomatic secondary tethering. Pregnancy and childbirth likewise are described as destabilizing events among women with cord tethering, although most of the examples in the literature have been women with various forms of spina bifida occulta.…”
Section: Spinal Cord Tetheringmentioning
confidence: 99%
“…Pregnancy and childbirth likewise are described as destabilizing events among women with cord tethering, although most of the examples in the literature have been women with various forms of spina bifida occulta. 1,15,20,40,45,71,76 Pang and Wilberger 67 proposed that assuming the lithotomy position for pushing and delivery places the tethered spinal cord under tension. Alternatively, the general ligamentous relaxation that occurs late in pregnancy may alter the mechanics of the spine, or changes in adiposity or in pelvic venous pressure may affect the marginally perfused tethered cord.…”
Section: Spinal Cord Tetheringmentioning
confidence: 99%
“…They compose 10% of the patients with spinal dysraphism at birth and are seen posteriorly in the cervical, thoracal, and lumbosacral regions 1 .…”
Section: Introductionmentioning
confidence: 99%